Visual task constraints influence head control and coordination variability in contact sport athletes - Zeff, S. R.; Hamill, J.; Martini, D.; van Emmerik, R. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
We sought to determine whether contact sport participation affects visual acuity, head control, and coordinative variability during locomotor tasks. Thirteen contact and eleven noncontact athletes completed treadmill walking tasks with and without a visual Landolt C task (identify open circle orientation). During baseline, head motion did not differ between groups, but contact athletes had reduced pelvis-thigh variability compared to noncontact athletes. During the visual condition only noncontact athletes reduced vertical head displacement which may reflect an adaptive motor strategy not present in contact athletes. These differences were accompanied by significantly reduced coordinative variability in contact athletes compared to noncontact athletes. These findings highlight motor alterations associated with contact sport status, which have the potential to impair perceptual awareness in sport-specific settings.